A New Direct 9-line Geometric Error Measurement Method for CNC Machine Tools. Issue 1 (March 2020) - Liu, Huanlao; Rasheed, Muzammil; Su, Miaojing; Liu, Can; Li, Xiaoli
Abstract: The existing line measurement methods are analyzed. In the process of obtaining the existing error parameters, the assumption conditions in the model developing are adopted, which makes the insufficient adaptability of the model and unreliable measurement results. A method for directly obtaining the error values of the machine tools have suggested by using a high-precision laser interferometer. The 9 lines at different places in the working space of the machine tool is proposed. A three-axes CNC vertical machining center was measured, which proved that the measurement process is easy to operate and the operation is relatively simple, which can be applied to actual industrial field measurement. This method is further popularized and can be used to verify other line measurement methods and check the error models, which has great practical application value.